2009
DOI: 10.1016/j.jcmg.2008.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Right Ventricular Tei Index in the Noninvasive Evaluation of Chronic Thromboembolic Pulmonary Hypertension Before and After Pulmonary Thromboendarterectomy

Abstract: These results demonstrate a correlation between RV Tei index and right heart hemodynamics (particularly PVR) in CTEPH. Because PVR is difficult to estimate noninvasively -- and yet correlates with disease severity -- the RV Tei index may be a valuable noninvasive parameter for monitoring disease severity in CTEPH and outcome after PTE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 24 publications
3
65
0
2
Order By: Relevance
“…Although the isovolumic phases of IVCT and IVRT are slightly longer when measured by TDI versus pulsed Doppler, it has been shown that TDI-determined Tei index (Fig. 3a) correlates well with the Tei index determined by flow Doppler, and thus represents a simple method of assessing RV myocardial performance with the advantage of simultaneous recording of systolic and diastolic velocity patterns [85,86].…”
Section: Myocardial Imaging Echocardiographymentioning
confidence: 86%
“…Although the isovolumic phases of IVCT and IVRT are slightly longer when measured by TDI versus pulsed Doppler, it has been shown that TDI-determined Tei index (Fig. 3a) correlates well with the Tei index determined by flow Doppler, and thus represents a simple method of assessing RV myocardial performance with the advantage of simultaneous recording of systolic and diastolic velocity patterns [85,86].…”
Section: Myocardial Imaging Echocardiographymentioning
confidence: 86%
“…Czernik et al [14] noted that RV MPI declined steadily in preterm non-BPD infants in the first 4 weeks, but remained elevated in those who subsequently developed BPD. It also correlates with PVR derived from invasive cardiac catheterisation [18]. TAPSE is a measure of RV contractile function and provides an estimate of longitudinal shortening [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…RVMPI has been evaluated for the assessment of LV and RV function in heart failure and PH. [26][27][28][30][31][32][33] Myocardial deformation parameters of the RV free wall, such as strain and strain rate, have been proposed as load-and heart motion-independent measures of RV function. [34][35][36] It has been suggested that echocardiographic indexes of RV function, including TAPSE, RVMPI, RVFAC, and IVA, are related to RV-PV coupling (E es /E a ) rather than to E es alone.…”
mentioning
confidence: 99%